2010
DOI: 10.1007/978-1-60327-323-7_30
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Assays for Characterization of Alternatively Spliced Isoforms of the Mu Opioid Receptor (MOR)

Abstract: Mu-opioid receptor (MOR) belongs to a family of heptahelical G-protein-coupled receptors (GPCRs). Studies in humans and rodents demonstrated that the OPRM1 gene coding for MOR undergoes extensive alternative splicing afforded by the genetic complexity of OPRM1. Evidence from rodent studies also demonstrates an important role of these alternatively spliced forms in mediating opiate analgesia via their differential signaling properties. MOR signaling is predominantly Giα coupled. Release of the α subunit from G-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…(Gris et al, 2010; Zhang et al, 2013) Similar to the eQTL patterns observed for KAT2B and CREBBP , rs9829896 was associated with OPRM1 expression in AAs ( P =0.016) but not in EAs ( P =0.12). The drug abuse protective rs9829896-C allele was associated with higher OPRM1 expression (Figure 2c).…”
Section: Resultsmentioning
confidence: 54%
“…(Gris et al, 2010; Zhang et al, 2013) Similar to the eQTL patterns observed for KAT2B and CREBBP , rs9829896 was associated with OPRM1 expression in AAs ( P =0.016) but not in EAs ( P =0.12). The drug abuse protective rs9829896-C allele was associated with higher OPRM1 expression (Figure 2c).…”
Section: Resultsmentioning
confidence: 54%
“…Forskolin is a labdane diterpene produced by the Indian coleus plant, and is commonly used in medical research to raise cAMP levels (Gris et al, 2010). Forskolin re-sensitizes cell receptors by activating adenylyl cyclase (AC) to catalyze the levels of cAMP.…”
Section: Stimulation Of Campmentioning
confidence: 99%